KETAHANAN NASIONAL DALAM PENDEKATAN MULTIKULTURALISME - Widisuseno, Iriyanto (Faculty of Humanities, Diponegoro University, 2013)
ABSTRACT Multiculturalism is a tool, and method, vehicle or the equivalent notion of ideology, function to enhance human dignity and self resilience. Since multiculturalism is a tool then the sense of culture or ideology embodied in the term multiculturalism should be viewed from the perspective of function for human life. Multiculturalism has always built based on the philosophical outlook of a nation on the meaning of life and life, and relationships with environment as well as the creator. Then every nation in giving practical meaning of multiculturalism will be colored by its philosophical outlook. The multicultural education paradigm led to the creation of attitudes of learners who want to appreciate, respect for ethnic, religious and cultural society. Then, too, multicultural education to give awareness to students that differences in ethnicity, religion and culture as well as the other does not become a barrier for students to unite and cooperate. Thus, Pancasila as an ideology of education is needed, especially considering the posture of Indonesia in the form of an archipelago, and pluralistic world is at a cross position. Key words: self resilience, multiculturalism, multicultural education.